The Influence Of Mutation And Promotion On Auditor Performance In The Bpkp Representative Office Of South Sumatra Province Through Job Satisfaction As An Intervening Variable - Ruby, Fazli; Yuliani, Yuliani; Karimudin, Yos; Hanafi, Agustina; WK, Wita Farla (Jurnal Ekonomi, 2024)
The phenomenon of mutation, promotion, and job satisfaction that has been explained above, is believed to have an influence on the performance of auditors in the Financial and Development Supervisory Agency (BPKP). Efforts to improve BPKP performance will be greatly influenced by the performance of each employee. This study aims to determine the effect of mutation and promotion on employee performance in the BPKP Representative Office of South Sumatra Province, through job satisfaction as an intervening variable. In this study, the author uses a quantitative approach. The sample in this study were all Auditors at the BPKP Representative Office of South Sumatra Province, taken using a saturated/census sampling technique. Primary data collection in this study was through distributing questionnaires to all Auditors at the BPKP Representative Office of South Sumatra Province. The data collection technique in this study used a questionnaire. From the results of the study that have been described in the previous chapter, there are several conclusions, including mutation has a positive and significant effect on Job Satisfaction of BPKP Employees of the South Sumatra Province Representative Office. Promotion has a positive and significant effect on Job Satisfaction of BPKP Employees of the South Sumatra Province Representative Office. Mutation has a positive and significant effect on Auditor Performance of BPKP Employees of the South Sumatra Province Representative Office. Promotion has a positive and significant effect on Auditor Performance at BPKP Representative Office of South Sumatra Province. Job Satisfaction has a positive and significant effect on Auditor Performance at BPKP Representative Office of South Sumatra Province. Mutation has a positive and significant effect on Auditor Performance through Job Satisfaction at BPKP Representative Office of South Sumatra Province. Promotion has a positive and significant effect on Auditor Performance through Job Satisfaction at BPKP Representative Office of South Sumatra Province.